Composition of nekton and jellyfishes communities and the results of trawl survey for estimation of abundance of pre-anadromous migrations pink salmon (Oncorhynchus gorbuscha) in the north-western Pacific Ocean in summer 2021 - A. N. Starovoitov; E. V. Gritsay; D. N. Chulchekov (Известия ТИНРО)
As a result, of a trawl survey performed in the Pacific waters of the Kuril Islands within the EEZ of the Russian Federation and outside the external border of the EEZ of the Russian Federation, the abundance and biomass of all representatives of nekton and macroplankton were determined. Peculiarities of the spatial distribution of massive representatives of pelagic nekton and jellyfish were revealed. According to the summer survey of the upper epipelagic layer of the Pacific waters, the abundance and biomass of Pacific salmon during their pre-anadromous migrations to the rivers of the Okhotsk Sea basin were taken into account and the main concentrations of mature pink salmon were outlined. During the survey, data on the biological state of salmon in mixed clusters were obtained and preliminary spatial differentiation of the early and late pink salmon stock belonging to different regions of the Okhotsk Sea was performed.